Collective efficacy and HIV prevention in South African townships. - Cain, Demetria; Pitpitan, Eileen V; Eaton, Lisa; Carey, Kate B; Carey, Michael P; Mehlomakulu, Vuyelwa; Harel, Ofer; Simbayi, Leickness C; Mwaba, Kelvin; Kalichman, Seth C (Journal of community health, 2013)
South African townships have high HIV prevalence and a strong need for collective action to change normative sexual risk behaviors. This study investigated the relationship between perceptions of individuals about collective efficacy in the community's ability to prevent HIV and their personal HIV risk behaviors. Men (n = 1,581) and women (n = 718) completed anonymous surveys within four Black African Townships in Cape Town, South Africa from June 2008 to December 2010. Measures included demographics, alcohol use, attitudinal and behavioral norms, sexual health communications, and sexual risk behaviors. In multivariate logistic regressions, men were more likely to endorse collective efficacy if they were married, drank less often in alcohol serving establishments, believed that fewer men approve of HIV risk behaviors, talk more with others about HIV/AIDS, and had more sex partners in the past month. Women were more likely to endorse collective efficacy if they drank alcohol less often, talked more with others about HIV/AIDS, had more sex partners in the past month, but reported fewer unprotected sex acts in the past month. Community level interventions that strengthen collective efficacy beliefs will have to consider both protective and risk behaviors associated with believing that the community is ready and capable of preventing HIV.
Keywords: Adolescent; Adult; Alcohol Drinking; Communication; Consumer Participation; Cross-Sectional Studies; Female; Health Knowledge, Attitudes, Practice; HIV Infections; Humans; Male; Risk-Taking; Sexual Behavior; Social Environment; Socioeconomic Factors; South Africa; Young Adult